Pattern of Occurrence and Management of Dual Malignancy: Our Institutional Experience - Sweety, Sweety; Singh, Pragya; Chophy, Atokali; Rastogi, Aviral; Sikdar, Debanjan; Ahuja, Rachit; Joseph, Deepa; Durgapal, Prashant; Gupta, Amit; Kumar Gupta, Manoj (Reports of Radiotherapy and Oncology, 2023)
Background: Management of dual malignancies is challenging in the present scenario of advanced techniques and increased life expectancy. Objectives: To determine the demographic and clinical profile of patients with dual malignancies and the management received. Methods: In this retrospective analysis of the data of patients presenting with histologically proven synchronous or metachronous dual malignancy, we evaluated the demographic and clinical profile of patients with dual malignancies and the management received. Results: In this study, 158 cases with multiple primary cancers, of whom 57 were synchronous and 101 were metachronous, were observed from January 2017 to December 2021. The maximum period for synchronous tumor occurrence was seen at 6 months (180 days). The interval of occurrence of metachronous tumors ranged from 1 to 15 years, with an average of 4.8 years for the entire group. Moreover, 73 (46.2%) were females, and 85 (53.8%) were males, with a male-to-female ratio of 1.2: 1. The most common site of primary tumor with dual malignancies was the head and neck (31%), followed by breast cancers (21%). The most frequent pathologic type was adenocarcinoma (40%), followed by squamous carcinoma (38%), hematopoietic and lymphoid tissues (7.5%), transitional cell carcinoma (6.3%), sarcomas and soft tissue tumors (2.5%). Conclusions: Even in complete clinical remission, every cancer patient must take into account the possibility of developing a second malignancy and must be closely monitored.